Exogenous application of salicylic acid and NPK promotes tomato growth parameters, yield, and nutraceutical quality under cold stress - Fozia; Gao YIKE; Anam ZAHID; Shahzad A. NAVEED; Kotb A. ATTIA; Arif A. MOHAMMED; Saeed A.S. CHISHTI; Muhammad UZAIR (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
The usage of biostimulants such as salicylic acid (SA) and NPK has emerged as an innovative practice for increasing crop production and quality. It plays a crucial role in the control of many physiological and metabolic processes. This experiment aimed to investigate the impact of SA and NPK treatment on the yield, growth, and quality characteristics of tomatoes grown in field conditions. The experiment structure laid out RCBD with three replications. Studied the effect of nine treatments of NPK (7 g/L), SA (0.05 mM, 0.1 mM, 0.5 mM, 1.0 mM), and combination of both (NPK+ 0.05 mM, NPK+ 0.1 mM, NPK+ 0.5 mM and NPK+ 1.0 mM) on two varieties of tomato. The foliar applications of SA, NPK, and their mixtures were administered during the planting phase, the onset of flowering, and the fruiting stage by maintaining intervals of 10 days after 15 days of transplanting. The response variables were yield (Plant height, number of fruits per plant, leaf area) fruit quality parameters (firmness, pericarp thickness, titratable acidity (TA), total soluble solids), nutraceutical quality parameters (Total sugars, ascorbic acid, non-reducing sugars, lycopene, β-carotene, reducing sugars, total phenols, and proline contents). The results indicate that foliar spray with SA and NPK boosts yield and phytochemical component production in tomato fruits compared to control. According to the findings, the treatments (NPK+ 0.5 mM and NPK+ 1.0 mM) showed the best results regarding bioactive compounds, yield, and quality parameters in both varieties of tomato under cold stress conditions.